PPID READINESS OF DEPARTMENT OF COMMUNICATION AND INFORMATICS IN PUBLIC INFORMATION SERVICE (Case in Bitung, North Sulawesi Province) - KESIAPAN PPID DINAS KOMUNIKASI INFORMATIKA DALAM PELAYANAN INFORMASI PUBLIK (Kasus di Kota Bitung, Provinsi Sulawesi Utara) - Syamsiah Amali (BPSDMP Kominfo Manado, 2016)
Law No. 14 of 2008 on Public Information, requires that the government must be transparent and accountable. This requirement becomes important to be implemented in all public institutions by forming the PPID. Department of Communication and InformaticsBitung town just formed PPID 2014. This study aims to identify the readiness of PPID in Department of Communication and Informatics in the public information services in the Bitung city. The approach of this research is qualitative descriptive research methods. The results of this study include finding, readiness of PPID Department of Communication & Informatics in public information services in the Bitungcity is still limited and inadequate, both of the facilities, infrastructures and human resources. The Barriers / constraints are in terms of budget, facilities, infrastructureand limited human resources. However, efforts continue to be made by Department of Communication and Infomatics to improve the Public Information service.Keywords: public institution, public information, accountability. Undang-undang Nomor 14 Tahun 2008 tentang Keterbukaan Informasi Publik, mensyaratkan agar pemerintahan bersifat transparan dan akuntabilitas. Persyaratan ini menjadi penting untuk diimplementasikan di semua Badan Publik dengan membentuk PPID. Diskominfo kota Bitung baru membentuk PPID tahun 2014. Penelitian ini bertujuan untuk mengidentifikasi kesiapan PPID Dinas Komunkasi Informatika dalam pelayanan informasi publik di kota Bitung.Pendekatan penelitian ini secara kualitatif dengan metode penelitian deskriptif. Pengumpulan data wawancara mendalam (indepth interview) dengan 8 informan di lingkungan Dinas Kominfo Kota Bitung dan Biro Humas Kota Bitung. Lokasi penelitian di Unit Pejabat Pengelola Informasi dan Dokumentasi (PPID) Kota Bitung. Hasil penelitian ini antara lain menemukan , kesiapan PPID Diskominfo dalam pelayanan informasi publik di kota Bitung masih terbatas dan belum memadai, baik dari sarana, prasana serta SDM.Hambatan/kendala dalam segi anggaran, sarana, prasarana dan SDM yang maih terbatas. Namun upaya-upaya terus dilakukan oleh Diskominfo untuk meningkatkan pelayanan Informasi Publik. Kata kunci: badan publik, informasi publik, akuntabilitas. Kata kunci: badan publik, informasi publik, akuntabilitas.